The intellectual structure of the information systems field: Research styles and publication patterns of North American and European paradigms - Ergüner Özkoc, Esma; Ahmet Kefkir, Teoman; Kırkbeşoğlu, Erdem (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2022)
This paper identifies the researches that have had the greatest impact on the Information Systems (IS) discipline and analyses the changes that have taken place in the intellectual structure of this discipline within the ongoing paradigmatic debates between Europe and North America. The methodology applies citation analysis and social network analysis to the articles published in four European and North American journals with the highest impact factors in the IS field. The findings of the study reveal a significant difference between the research styles and publication patterns of European and North American research traditions.